Globalization, Technological Developments, and the Work of Fiscal Termites - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 2000)
Deepening globalization and associated or parallel technological and institutional developments are creating conditions which may reduce the industrial countries' ability to sustain high levels of taxation. The paper identifies and discusses eight trends which may generate revenue falls. It also discusses some measures that might neutralize or reduce the impact of these trends.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet